Pemanfaatan Media Sosial Humas pada Lembaga Pendidikan serta Peningkatan Citra Lembaga - Lieyani, Yanezra; Natalia, Liza; Setiyadi, Bradley (Universitas Batanghari Jambi, 2025)
This research aims to explore the use of public relations social media in educational institutions as well as improving the image of the institution. This research applies a library research approach, a method for collecting data from various written sources that are relevant to the research topic. A literature review of the use of social media in education has depicted a variety of purposes including promoting events and activities, conveying important information to parents and students, interacting directly with followers, sharing instructional content, highlighting achievements and awards, and forming online communities. The use of social media for public relations purposes in various educational institutions makes contributions, such as expanding the scope of communication, stimulating greater community involvement and interaction, increasing the institution's positive reputation, as well as increasing information accessibility and the level of transparency for various stakeholders.